Perceptions of African musical arts education in foundation and intermediate phases in government schools as seen through the South African academy since 2011: an exploration through meta-ethnography - Chirombo, Ilana Elize Caroline (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
The aim of this study is twofold: first, to understand meta-ethnography as a tool of synthesis; second, to use this methodology to explore perceptions of African musical arts education in the Foundation and Intermediate Phases in government schools in South Africa after 2011. Meta-ethnography is a methodology used to synthesise qualitative material by means of seven distinct phases: getting started; deciding what is relevant to the initial interest; reading the studies; determining how they are related; translating the studies into one another; weaving them together into a synthesis; and expressing the synthesis. This study synthesises five articles discovered through a deep search of the literature. Through the process of synthesis, a narrative emerges that connects past prejudice in music education in South Africa to present day educational inequality, one that looks towards a future in which children's agency is harnessed in the multicultural world we live in to teach music in a relevant, contextual way. The synthesis extracts perceptions on colonialism and apartheid; educational access; post-apartheid curricula; music education pedagogies; informal music making; children's games and agency; into the classroom; and how to assess. These themes weave a clear perspective on African musical arts education, and a reciprocal synthesis of the views of the articles' authors. This study finds meta-ethnography to be a rigorous, understandable methodological tool for qualitative synthesis, one which serves the purpose of researchers, no matter the depth of their engagement with the synthesis.
Keywords: Music Instruction and study -- South Africa; Music of Africa; Arts, African; Traditional knowledge; Qualitative research; Ethnography